Tanshinone IIA attenuates interleukin-17A-induced systemic sclerosis patient-derived dermal vascular smooth muscle cell activation via inhibition of the extracellular signal-regulated kinase signaling pathway - Liu, Mengguo (2015)
OBJECTIVE: Salvia miltiorrhiza has long been used to treat systemic sclerosis. Tanshinone IIA, one of the phytochemicals derived from the roots of Salvia miltiorrhiza, exhibits multiple biological activities. The present study aimed to investigate whether tanshinone IIA has an effect on the interleukin-17A-induced functional activation of systemic sclerosis patient-derived dermal vascular smooth muscle cells. METHODS: Systemic sclerosis patient-derived dermal vascular smooth muscle cells were incubated with various dosages of tanshinone IIA in the presence of interleukin-17A or the serum of systemic sclerosis patients. Cell proliferation was assessed using Cell Counting Kit-8. The expression of collagen 1 and 3 in cells was evaluated by immunofluorescence. Cell migration was measured using a transwell assay. The expression of phospho-extracellular signal-regulated kinase was detected by Western blotting. RESULTS: Our data demonstrate that tanshinone IIA exerts an inhibitory effect on interleukin-17A-induced systemic sclerosis patient-derived dermal vascular smooth muscle cell proliferation, collagen synthesis and migration. CONCLUSION: These findings suggest that tanshinone IIA might serve as a promising therapeutic agent for the treatment of systemic sclerosis.